IMPLEMENTATION OF ICE BREAKING IN SPEAKING SKILL AT SMA KARTIKA XX-1 MAKASSAR - Aguisty Lowu, Tiwi Arisca; Rampeng, Rampeng; Fansury, Andi Hamzah (Publikasi dan UKI Press UKI Toraja., 2023)
Tiwi Arisca Aguisty Lowu, 2023. Implementation of Ice Breaking in Speaking Skill at SMA Kartika XX-1 Makassar. Skripsi, English Language Education Study Program, Faculty of Education and Literature, Bosowa University (Supervised by Andi Hamzah Fansury and Rampeng). This study aimed to find out whether the implementation of Ice Breaking improve the student speaking skill. This study focused on pre-experimental research one group pre-test and post-test. The population in this study were students of class X MIPA 4 SMA Kartika XX-1 Makassar and it consist of 20 students as the population. Data obtained from writing test pre-test, treatment, post-test, and questionnaire. The results of this study used inferential analysis of the t-test by SPSS 25 version which showed a significant effect on the students? mean score speaking skill between the pretest and post-test. The mean score of the students? speaking enhanced from 40.60 in the pretest to 72.60 in the posttest. The significance value calculated 0.000 was smaller than 0.05 (P-value = 0.000 < 0.05). Thus, it can be concluded that there are significant influences of using Ice Breaking method on students’ speaking skill.